Implementation of the Kullīyat al-Mu‘allimīn Al-Islāmīyah Curriculum in Improving the Quality of Graduates in Islamic Boarding School - Musthofa, M Arif; Yamin, Martinis; Badarussyamsi, Badarussyamsi (Journal of Educational Research, 2023)
This article reveals a situation, Kullīyat al-Mu‘allimīn Al-Islāmīyah Gontor Curriculum Planning in Improving the Quality of Graduates which is carried out using the I'dad Tadris, I'dad Madhi (material) and I'dab Maknawi (meaning) methods which are not just knowledge but wisdom. Implementation of the curriculum is in accordance with the use of an integral curriculum and evaluation is carried out carefully and in detail. The feasibility study was implemented in the context of increasing the number of ustadz and subjects taught. This is important to do so that you can find out the condition of the number of teachers, teacher abilities, and even obstacles. Evaluations are carried out by the person in charge of Kullīyat al-Mu‘allimīn Al-Islāmīyah in various ways, either daily, weekly, monthly, semi-annually or annually. All of this is done to ensure that the quality of graduates meets expectations. Artikel ini mengungkap suatu  keadaan, Perencanaan Kurikulum Kullīyat al-Mu‘allimīn Al-Islāmīyah Gontor Dalam Meningkatkan Mutu lulusan yang dilakukan dengan metode I’dad tadris, I’dad madhi (materi) dan I’dab maknawi (makna) yang tidak hanya sekedar pengetahuan melainkan hikmah. Pelaksanaan kurikulum sesuai dengan penggunaan kurikulum yang integral serta evaluasi yang dilakukan dengan teliti dan detail. Studi kelayakan diterapkan dalam konteks penambahan jumlah ustadz dan mata pelajaran yang diampu. Ini penting dilakukan agar dapat mengetahui keadaan jumlah guru, kemampuan guru, bahkan kendalanya. Evaluasi dilakukan oleh Penanggung jawab Kullīyat al-Mu‘allimīn Al-Islāmīyah secara bervariasi, baik harian, mingguan, bulanan, semesteran, maupun tahunan.  Semua ini dilakuan untuk memastikan tercapainya mutu lulusan yang sesuai dengan harapan.